Geosynonyms in the seventeenth-century Croatian dictionary: about some Italianisms - Ljubičić, Maslina (Array, 2008)
Ivan Belostenec's Latin-Croatian and Croatian-Latin two-volume dictionary, written in the 17th century, was edited more than sixty years after its author's death. Belostenec's lexicographic orientation is defined as tridialectal ; therefore his dictionary, consisting of kajkavian, chakavian and štokavian components, offers many geosynonyms. The diatopic variants of Dalmatia are present in the dictionary but not many of them are Italianisms.